The World of the Ladies’ Court in the Modern Era - Introduction - Popiołek, Bożena; Jakuboszczak, Agnieszka (Sensus Historiae, 2026)
Research on women’s courts - and, by extension, on the standard of living of the magnates and nobility - has a long tradition, yet it continues to spark interest, and many issues require in-depth study and verification of established facts. The articles collected in this issue of "Sensus Historiae" constitute an important contribution to research on the history and role of women’s courts and their patronesses in the early modern era.